Poesía y espiritualidad en una secuencia latina medieval. A propósito del Planctus cygni (Argos, 2025)
The anonymous Planctus Cygni, composed between IX-X centuries, is a magnificent exponent of the monastic medieval literature where deep spiritual experiences and delicate poetic feelings meet. In this work, we try to find out the latent sense in the allegory of the swan that flies into Heaven.
Keywords: sequences; medieval latin literature; medieval latin poetry; lyric poetry; monasticism